Conventional cervical smears disclose histoplasmosis: a case report - S., Zohra Fatima; Fatima, Ayesha; Hussain, Syed Arshad; Fatima, Arshia; Siddiqua, Syeda Ayesha (International Journal of Research in Medical Sciences, 2025)
Histoplasmosis is an uncommon fungal infection caused by Histoplasma capsulatum, often presenting as a pulmonary disease in endemic regions. Extrapulmonary manifestations, particularly involving the genitourinary tract, are exceedingly rare and pose diagnostic challenges. This case report discusses a 36-year-old female who presented with a one-year history of foul-smelling white vaginal discharge, abdominal discomfort, and lower back pain. Cytological analysis of a pap smear revealed extracellular yeast-like cells consistent with histoplasma capsulatum. The smear was classified as negative for intraepithelial lesion or malignancy (NILM). Routine blood tests and organ function tests were normal, and further investigations were recommended to exclude systemic histoplasmosis, including serological detection of anti-H and anti-M antibodies using histoplasmin. The rarity of this presentation emphasizes the importance of considering fungal infections in the differential diagnosis of chronic gynecological symptoms, particularly in regions where histoplasmosis is endemic. Pap smear cytology, a cost-effective and accessible diagnostic tool, was pivotal in identifying the pathogen. Differential diagnoses such as candidiasis and cryptococcosis were ruled out based on the characteristic morphological features of histoplasma capsulatum. Comprehensive management, including systemic screening and potential antifungal therapy, is essential to prevent disease progression. This case underscores the need for heightened clinical awareness and a multidisciplinary approach to diagnose and manage rare fungal infections in gynecological practice. Additionally, it highlights the diagnostic utility of cytological methods in identifying atypical pathogens beyond routine cervical cancer screening.